Perlindungan Hak atas Kebebasan Beragama dan Berkeyakinan bagi Kelompok Minoritas Agama dan Aliran Kepercayaan (Studi Kasus di Provinsi Sulawesi Utara) - Oksimana Darmawan (Jurnal HAM, 2013)
The questions in this research are: 1) how do the regulation protect the rights of minority to freedom of religion and belief at the provincial level; 2) whether the existing regulations are in line with the instruments of human rights; and 3) how is the reality of people living in the context of harmony between religious groups. The purposes of this study are: 1) to find out the regulation of freedom of religion and belief for minority groups; 2) to find out whether regulations are in conflict with the human rights instruments in terms of freedom for religious minority groups; and 3) to find out the reality of people's life in the context of harmony among believers. The method of this research is qualitative-descriptive research that generates descriptive data in the form of written word or spoken, and people's behavior that can be observed. Several conclusions in this research are: 1) Regulatory policy in North Sulawesi rules that any religious organizations other than the six religions, namely Islam; Catholic; Protestants; Buddha; The Hindu; and Confucius, is considered to be a social organization (beliefs) that can be registered to the government, through the Ministry of culture and tourism; 2) instruments of human rights have been accomodated on one of the principles of human rights, i.e. participation, through the inter-faith cooperation forum (FKUB and BKSAUA); and 3) the reality of community's life in the context of harmony between religious groups is tied by the rope of fraternity.